1979
DOI: 10.1007/bf02676360
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of processing on the content and composition of free sterols and sterol esters in soybean oil

Abstract: The content and composition of free sterols and sterol esters in crude soybean oil and in oils from different stages of two continuous refining systems were determined. The sterols were isolated by preparative thin layer chromatography and analyzed by gas chromatography with cholesterol as an internal standard. The free sterols in one of the degummed oils amounted to 3.1 mg/g and were diminished to 1.8 mg/g oil by the De Laval Short-Mix refining process. The content of free sterols of the other degummed oil wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 18 publications
2
13
0
1
Order By: Relevance
“…The average values of 76% of total free sterols and 24% esterified in refined soybean oils agree between the present study and that of Johansson (1979b). The average results for olive oil in our analysis agreed remarkably well with the average proportion of free and esterified sterols in eight Italian olive oils as determined by Grob et al (1990) using LC-GC (Table 3).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The average values of 76% of total free sterols and 24% esterified in refined soybean oils agree between the present study and that of Johansson (1979b). The average results for olive oil in our analysis agreed remarkably well with the average proportion of free and esterified sterols in eight Italian olive oils as determined by Grob et al (1990) using LC-GC (Table 3).…”
Section: Resultssupporting
confidence: 92%
“…For example, refining has been reported to decrease the total sterol content of crude oils and to increase the proportion of esterified sterols (Kochhar, 1983). Data on the free and esterified sterol content of refined and/or commercially distributed oils have been presented for soybean (Milkova et al, 1977a;Johansson, 1979b), corn (Worthington and Hitchcock, 1984;Milkova et al, 1977b), olive (Dimitrios and Ioanna, 1986;Grob et al, 1990), and sunflower (Milkova et al, 1977b) oils. Kochhar (1983) compiled data for several crude and refined oils, but many reports are dated and sterol values were from colorimetric, not chromatographic, analysis.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, they have a great importance in adulteration detection (Feinberg etal., 1987;Gordan et al, 1989 andJohansson et a!., 1979). This chemical components are also used for varietal characterisations (Castang et al, 1976 andKiosseglou et al, 1989), and are reported to be indicators of the best period of harvest (Fiorino etal., 1991).…”
Section: The Evolution Of the Sterolic Compositionmentioning
confidence: 99%
“…However, they have been performed several years ago [4][5][6], before the first commercialisation of genetically modified organisms (GMO). As nowadays GMO have been a topic of discussion among the scientific community and consumers, and since GM crops are widely used to obtain edible oils, the oilseeds from RR soya bean were the subject of the present study.…”
Section: Introductionmentioning
confidence: 99%